Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00001432-200106000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and chemokines in the immune response to hepatitis C infection

Abstract: Over 170 million people are infected with the hepatitis C virus worldwide, resulting in a large disease burden and significant mortality. Hepatitis C virus is rarely cleared in the acute phase of the infection and most patients become chronically infected; a proportion of these patients develop progressive liver disease and fibrosis. The outcome of infection depends on the immune responses of both the innate and cognate immune systems, and these in turn are orchestrated by networks of cytokines and chemokines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 77 publications
1
29
0
5
Order By: Relevance
“…in which within the normal liver hepatic stellate cells 41 and hepatocytes, 42 for example, release chemokines into the space of Dissé, we hypothesize that these chemokines can be taken up by LSEC from the basal side and are then presented on the luminal side, supporting CD4 ϩ T cell trafficking. Transmigrating T cells might rapidly remigrate, receive suppressive signals upon transmigration, 43,44 or subsequently interact with tolerogenic Ito cells.…”
Section: Discussionmentioning
confidence: 83%
“…in which within the normal liver hepatic stellate cells 41 and hepatocytes, 42 for example, release chemokines into the space of Dissé, we hypothesize that these chemokines can be taken up by LSEC from the basal side and are then presented on the luminal side, supporting CD4 ϩ T cell trafficking. Transmigrating T cells might rapidly remigrate, receive suppressive signals upon transmigration, 43,44 or subsequently interact with tolerogenic Ito cells.…”
Section: Discussionmentioning
confidence: 83%
“…Our results suggest a role for immune-mediated apoptosis of hepatocytes by infiltrating T cells. HCV infection induces T cell response and a number of inflammatory mediators, including cytokines and chemokines (32). It has demonstrated that TRAIL expression is up-regulated in T cells activated by anti-CD3 (19,25,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…CCL5/CCR5 interaction is likely to be important during hepatitis C virus infection, where T cells are recruited to the liver parenchyma to mediate clearance of HCVinfected hepatocytes 95 . Consistent with this hypothesis, RANTES-403 G/A SNP was observed to decrease risk of severe inflammation in Hepatitis C virus-seropositive patients heterozygous or homozygous for the RANTES promoter alleles -403*A 96,72 .…”
Section: Other Diseasesmentioning
confidence: 99%